2016
DOI: 10.1371/journal.pone.0158720
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Disability in Older Japanese Adults

Abstract: The prevalence of disability is increasing due to an expanding aging population and an increasing incidence of chronic health problems. Cognitive impairment may predict the development of disability in older adults. Therefore, we examined the association of mild cognitive impairment (MCI) and/or general cognitive impairment (GCI, defined as a Mini Mental State Examination [MMSE] score of 20–23) with the development of disability in a cohort of Japanese community-dwelling older adults. A total of 4290 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 40 publications
2
73
2
Order By: Relevance
“…For cognitive function variables, the average MMSE score (26.1) was similar to that of a previous study (25.6), which used a home‐visit survey with all older adults living in one city with an adequate response rate (92.3%). The prevalences of mild (14.1%) and global cognitive impairment (13.8%) were not remarkably different from a previous study (17.4% for mild cognitive impairment, 13.9% for global cognitive impairment) . Additionally, no significant associations were observed for the distance to the screening site with MMSE scores and the incidence of such cognitive impairments.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…For cognitive function variables, the average MMSE score (26.1) was similar to that of a previous study (25.6), which used a home‐visit survey with all older adults living in one city with an adequate response rate (92.3%). The prevalences of mild (14.1%) and global cognitive impairment (13.8%) were not remarkably different from a previous study (17.4% for mild cognitive impairment, 13.9% for global cognitive impairment) . Additionally, no significant associations were observed for the distance to the screening site with MMSE scores and the incidence of such cognitive impairments.…”
Section: Discussioncontrasting
confidence: 75%
“…The prevalences of mild (14.1%) and global cognitive impairment (13.8%) were not remarkably different from a previous study (17.4% for mild cognitive impairment, 13.9% for global cognitive impairment). 29 Additionally, no significant associations were observed for the distance to the screening site with MMSE scores and the incidence of such cognitive impairments. However, Harada et al suggested that subjective cognitive impairments indirectly influence screening participation mediated by motivational factors.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…One strength of the current study is that we used data from full‐mouth assessments of periodontal status involving examinations of six sites on all teeth, allowing us to define periodontitis by two commonly used case definitions as well as calculate PISA. Another distinction is that our outcome includes MCI, which has attracted attention because of its increasing prevalence and association with a high risk of dementia and disabilities …”
Section: Discussionmentioning
confidence: 99%
“…This method was validated against an HRS substudy of Alzheimer disease and dementia that used an extended neuropsychological assessment as well as expert clinician adjudication to obtain gold standard diagnoses of normal cognition, CIND, and dementia. In the validation study, the 27-point scale classified individuals as normal cognition (scores, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and CIND (scores, 7-11). Scores lower than 7 indicated dementia, and these individuals were, therefore, excluded from the present study.…”
Section: Operationalization Of Physical Frailty and Cognitive Impairmentmentioning
confidence: 99%